THE EFFECTS OF READING FROM THE SCREEN ON THE READING MOTIVATION LEVELS OF ELEMENTARY 5TH GRADERS - (:unkn) unknown (TURKISH ONLINE JOURNAL EDUCATIONAL TECH-TOJET, 2012)
This study aims to explore the effects of reading from the screen on elementary 5th grade students' reading motivation levels. It used the randomized control-group pretest-posttest model, which is a true experimental design. The study group consisted of 60 students, 30 experimental and 30 control, who were attending the 5th grade of a public elementary school in Sakarya during the second term of the 2010-2011 school year. Three narrative and three expository texts were selected from the 6th and 7th themes of the Turkish text book which was used in this school. The texts were typed on the computer to be used with the experimental group. Data were collected by using the reading motivation scale designed by the researcher. The results showed that the reading motivation levels of students who read the texts from the screen were significantly lower than those of students who read the printed material, both in the subscales and the overall scale.
Keywords: Reading; Reading from the Screen; Motivation; Reading Motivation; CHILDRENS; COMPREHENSION; ENGAGEMENT